Identification of recurrent pathogenic alleles using exome sequencing data: Proof-of-concept study of Russian subjects - Orlov, Igor E.; Laidus, Tatiana A.; Tumakova, Anastasia V.; Yanus, Grigoriy A.; Iyevleva, Aglaya G.; Sokolenko, Anna P.; Bizin, Ilya V.; Imyanitov, Evgeny N.; Suspitsin, Evgeny N. (European journal of medical genetics, 2022)
Whole exome sequencing (WES) is a powerful tool for the cataloguing of population-specific genetic diseases. Within this proof-of-concept study we evaluated whether analysis of a small number of individual exomes is capable of identifying recurrent pathogenic alleles. We considered 106 exomes of subjects of Russian origin and revealed 13 genetic variants, which occurred more than twice and fulfilled the criteria for pathogenicity. All these alleles turned out to be indeed recurrent, as revealed by the analysis of 1045 healthy Russian donors. Eight of these variants (NAGA c.973G>A, ACADM c.985A>C, MPO c.2031-2A>C, SLC3A1 c.1400T>C, LRP2 c.6160G>A, BCHE c.293A>G, MPO c.752T>C, FCN3 c.349delC) are non-Russian-specific, as their high prevalence was previously demonstrated in other European populations. The remaining five disease-associated alleles appear to be characteristic for subjects of Russian origin and include CLCN1 c.2680C>T (myotonia congenita), DHCR7 c.453G>A (Smith-Lemli-Opitz syndrome), NUP93 c.1162C>T (steroid-resistant nephrotic syndrome, type 12), SLC26A2 c.1957T>A (multiple epiphyseal dysplasia) and EIF3F c.694T>G (mental retardation). These recessive disease conditions may be of particular relevance for the Russian Federation and other countries with a significant Slavic population.